Harpe og sverd Litteraturhistoriske essay om den norske balladen - Solberg, Olav (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
" This is a collection of essays about the Norwegian ballade, but it also includes ballads from the other Nordic countries. Many perceive the Norwegian ballad as something very close to what is considered the Norwegian soul, however the genre of the ballad dates back to the 1100 century in Europe. In the first essay the author will shed light on the duality of the origin of the ballad. In the second essay, the author writes about the Norwegian ballade, where they arose, how they lived on and looks into what kind of tradition they represent. Trolls and ballads are topics of the third essay, and in the fourth essay the author takes a closer look at two Danish song- and ballad books, namely Hundreviserboka by Anders Sørensen Vedel and the sequel, Tohundreviserboka, by Peder Syvs. The fifth essay is about ballads and identity. A central question being asked here, is how both poets and tradition help establish the identity of the actors in the ballade. Furthermore, sixth essay focuses on mythical nature in ballads. The so-called jester ballads (Skjemteballadar), have long been invalidated by researchers. In the seventh essay, however, the author presents these ballades in relation to theories of comedy and laughter. Finally, the eighth essay the author presents some central European ballads."